(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2011)
In this work, an attempt was made to synthesize chalcone 3-(Substitutedphenyl)-N-(4H-1, 2, 4-triazol-4-yl) acrylamide by condensation of substituted benzaldehyde with N-(4H-1,2,4-triazol-4-yl) acetamide under basic conditions. A simple condensation reaction of substituted benzaldehyde and N-(4H-1, 2, 4-triazol-4-yl) acetamide using Sodium hydroxide as a base was carried out for the study. The synthesized chalcone derivative was characterized by FTIR, 1H-NMR & 13C-NMR and studied for their Antimicrobial and Antifungal activities and compared with the standard drugs, some compound of the series exhibited promising anti-microbial and anti-fungal activity compared to standard drugs.